The effects of combined endurance training of different intensities and resistance training on bone mineral density, microstructure and mechanical properties of rats - Mo, Ting; Zhang, Xin; Zhao, Yueming; Li, Guangxin; Zhang, Zhanjia; Hou, Shilun (Frontiers in Endocrinology, 2026)
ObjectiveTo explore the effects of different intensities of endurance training combined with resistance training on the bones of growing male rats, and to provide the optimal exercise plan for bone mineral accumulation in adolescents.MethodsThirty 6-week-old male Sprague-Dawley rats were randomly divided into 5 groups: control (C), resistance training (R), low-intensity endurance + resistance (LR), moderate-intensity endurance + resistance (MR), and high-intensity interval + resistance (HR). After 8 weeks of exercise intervention, the bone mineral density, bone microstructure, bone mechanical properties and bone remodeling of rats were assessed. One-way analysis of variance (ANOVA) was used to test the results obtained by the detection methods.ResultsThe body weight of the exercise group was lower than that of the control group. The endurance and resistance training group (LR/MR/HR) had significantly higher bone mineral density than the control group (p’s < 0.05). There was no difference in bone metabolism markers among the groups. In the result of bone volume fraction, only the MR group was significantly higher than the control group (p = 0.03); the number of trabeculae showed statistical differences in the LR group and the MR group (p’s < 0.05). Each exercise group showed significantly higher maximum load and fracture stress than the control group (p’s ≤ 0.001), but no difference in maximum strain was shown.ConclusionCombined endurance and resistance training improved bone mineral density and mechanical strength in growing male rats, with moderate-intensity endurance training showing the most consistent improvements in bone microarchitecture.